Spark ablation metal nanoparticles and coating on TiO2 in the aerosol phase - B. Gfeller; M. Becker; A. D. Aebi; N. Bukowiecki; M. Wyss; M. Kalberer (Aerosol Research)
Generation and characterisation of metal nanoparticles (NPs) in the aerosol phase have gained attention in recent years due to their significant potential in applications as diverse as catalysis, electronics or energy storage. Despite the high interest in NPs, it remains challenging to obtain detailed quantitative information with conventional aerosol analysis instruments on size, number concentration, coagulation behaviour and morphologies, which are key to understand their properties. In this study we generated NPs from four metals – Au, Pt, Cu and Ni – via spark ablation in the aerosol phase, which allows the production of NPs as small as 1 nm in high quantities and purity. Particles were characterised with transmission electron microscopy (TEM), scanning transmission electron microscopy (STEM) and energy-dispersive X-ray spectroscopy (EDX) as well as online aerosol particle size distribution measurement techniques. Particle size modes for the four metals ranged between 3 and 5 nm right after generation. Differences in number and size of particles generated can be rationalised with thermodynamic properties of the metals such as melting point combined with their oxidative properties. The four metal NPs were also coagulated with larger TiO2 NPs of about 120 nm size, and the metal surface coverage of the TiO2 particles was characterised with electron microscopy and EDX. This detailed characterisation of NPs mixtures will be essential for a fundamental understanding of spark-ablation-generated particles and their applications for material sciences.